The Implementation Profile of The Science Literacy Movement in Elementary Schools - I Made Wiguna Yasa; I Komang Wisnu Budi Wijaya; I Putu Oktap Indrawan; Ni Made Muliani; Ni Wayan Sri Darmayanti (Universitas Pendidikan Ganesha, 2022)
The Science Literacy Movement was programmed by the Ministry of Education and Culture in 2017. In fact, the scientific literacy of Indonesian students is still in the low category, still below the average PISA completeness score. Based on these problems, it is important to understand the Science Literacy Movement in schools, especially elementary schools. This study aims to analyze the process, quality, and constraints of the implementation of the Science Literacy Movement in Elementary Schools. This research is classified as a mixed method. The mixed research design used by the researcher is an explanatory design. The subject of this research is the Science Literacy Movement program in each educational unit in the research location. The research instrument used was an evaluation questionnaire on the implementation of the Science Literacy Movement and interview guidelines. Data were analyzed descriptively. The results of the study stated that all schools had implemented the Science Literacy Movement but had not touched all aspects of the Science Literacy Movement; the quality of the implementation of the scientific literacy movement in schools as a whole is good; and the constraints experienced related to the Covid-19 pandemic situation, limited budget, limited infrastructure, low learning motivation, and lack of guidance from various parties. The implication of this research is that the Science Literacy Movement needs to be done holistically and creatively so that it can be implemented in offline and online learning.